Iterative Design and Monitoring for Adaptive Management: How Causal Link Monitoring can help - Britt, Heather; Hummelbrunner, Richard; Green, Jackie (Better Evaluation, 2018)
Development actors are embracing the concept and practice of adaptive management, using evidence to inform ongoing revisions throughout implementation. In this guest blog, Heather Britt, Richard Hummelbrunner and Jackie Greene discuss a practical approach that donors and partners can use to agree on what’s most important to monitor as a project continues to evolve.

Causal Link Monitoring - Better Evaluation (Better Evaluation)
Causal Link Monitoring (CLM) integrates design and monitoring to support adaptive management of projects. CLM helps project planners and managers identify the processes that are required to achieve desired results, and then to observe whether those processes take place, and how. Result-producing processes specify the causal links between results in a logic model or results framework—in other words, the processes between results. CLM focuses on how specific individuals or organizations use one result to achieve another result. Steps in Causal Link Monitoring In CLM, planners start by creating a logic model to help document predictable, agreed-upon elements of the project. Next, they refine the causal links by describing the processes that will transform results at one point in the causal chain to the next. Planners are often less certain about these result-producing processes. Finally, the CLM logic model is enhanced with information about two important sources of uncertainty, contextual factors that may influence the project and diverse perspectives on the problem and its solution. The process can be broken down into seven steps, three for project design, three for monitoring, and a final step in which monitoring data informs redesign: Build a logic model. Identify assumptions about causal links. Enhance the logic model with diverse perspectives and contextual factors. Prioritize areas of observation. Collect monitoring data. Interpret and use monitoring data for adaptive management. Revise the logic model.

Causal Link Monitoring - Britt, Heather; Hummelbrunner, Richard; Greene, Jacqueline (2017)
Causal Link Monitoring (CLM) 1 integrates design and monitoring to support adaptive management of projects. CLM helps project planners and managers identify the processes that are required to achieve desired results, and then to observe whether those processes take place, and how. Result-producing processes specify the causal links between results in a logic model or results framework—in other words, the processes between results.2 CLM focuses on how specific individuals or organizations use results to achieve other results. In CLM, planners start by creating a logic model to help document predictable, agreed-upon elements of the project. Next, they refine the causal links by describing the processes that will transform results at one point in the causal chain to the next. Planners are often less certain about these resultproducing processes. Finally, the CLM logic model is enhanced with information about two important sources of uncertainty, contextual factors that may influence the project and diverse perspectives on the problem and its solution.